Emigration of Brazilian doctors to the United States of America - Mota, Nancy Val y Val Peres da (2019)
This article considers, initially, the mobility of doctors throughout the world from a bibliographic database collection and identifies the lack of information regarding Brazilian doctors. The aim is to analyze aspects that determine the emigration of Brazilian doctors to the United States of America. The methodology is based on bibliographic research using the keywords brain drain, medical migration, physicians migration, data migration physicians; identification of articles related to the emigration of doctors throughout the world; elaboration and validation of the questionnaire “Emigration Motives”; identification of doctors that emigrated, using the “snowball” technique; sending of the questionnaire by e-mail to the doctors that emigrated to the USA; tabulation of the forwarded answers; Skype interviews aiming at the validation and illustration of the results obtained in the questionnaire. Initially, the doctors choose to emigrate for personal motives (family, professional opportunities, and, in general, absence of language barriers); when established in the USA, they experience a new way of life that makes them stay (better work condition, quality of life, family and general opportunities); external motives become the cause for staying in the USA (insecurity, professional, political and economic scenarios). The conclusion is that an emigrational process of Brazilian doctors to the USA exists and, at first, the reason to emigrate is not well defined; salary is not mentioned as a primary reason; the presence of the family eases the stay in the country; the proficiency in the English language is fundamental and necessary to restart the professional life as a recently graduated in medicine since there isn’t an university degree or medical specialty degree validation.